Study on the Effectiveness of Banana Peel Coagulant in Turbidity Reduction of Synthetic Wastewater - Priyatharishini, Mardarveran; N. M., Mohktar; Risky Ayu, Kristanti (Penerbit UMP, 2019)
Coagulation is an effective, simple and widely practiced water treatment method. However, the usage of chemical coagulant pose detrimental effect on living organism and human health as well as producing large amount of toxic sludge. This study describes the utilization of banana peel as a natural coagulant for the treatment of household wastewater. The natural coagulant extracted from banana peel was prepared by using simple extraction method. Synthetic wastewater was used in this study to imitate the medium strength household wastewater. The parameters investigated in this study were pH of wastewater, coagulant dosage, and solvent of extraction. The effectiveness of the natural coagulant was evaluated based on the reduction of turbidity during the treatment process. The treatment of synthetic wastewater using banana peel coagulant was found to be the most effective at pH 1 and dosage of 100 mg/l whereas the most effective solvent to extract this type of fruit waste is sodium hydroxide (NaOH). In present work, it can be concluded that the banana peel coagulant was highly feasible in removing turbidity of the synthetic wastewater with removal efficiency of 88% under optimum condition.